2010
DOI: 10.1007/s12013-010-9124-x
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Leukocyte Mitochondrial Membrane Potential in Type 1 Diabetes Families

Abstract: Proper cellular function requires the maintenance of mitochondrial membrane potential (MMP) sustained by the electron transport chain. Mitochondrial dysfunction is believed to play a role in the development of diabetes and diabetic complications possibly because of the active generation of free radicals. Since MMP can be investigated in clinical settings using fluorescent probes and living whole blood cells, mitochondrial membrane alterations have been observed in some chronic disorders. We have used the mitoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…These data collectively suggested that Exe and LIRA offer their cardioprotective effects possibly through inhibition of oxidative stress and mitochondria-dependent apoptosis. Involvement of mitochondrial injury in GLP-1 agonist-offered protection against glucose toxicity received further supports by MMP and is in line with the notion of disturbed preservation of MMP by mitochondrial respiratory chain in diabetes [ 40 , 41 ]. It is plausible to speculate that sustained MMP in the face of Exe and LIRA treatment contributes to the inhibition of ROS generation.…”
Section: Discussionmentioning
confidence: 56%
“…These data collectively suggested that Exe and LIRA offer their cardioprotective effects possibly through inhibition of oxidative stress and mitochondria-dependent apoptosis. Involvement of mitochondrial injury in GLP-1 agonist-offered protection against glucose toxicity received further supports by MMP and is in line with the notion of disturbed preservation of MMP by mitochondrial respiratory chain in diabetes [ 40 , 41 ]. It is plausible to speculate that sustained MMP in the face of Exe and LIRA treatment contributes to the inhibition of ROS generation.…”
Section: Discussionmentioning
confidence: 56%
“…Mitochondrial dysfunction is demonstrated to be implicated in the pathological progression of diabetes and diabetic complications. 6 Mitochondrial homeostasis disorder and mitochondrial membrane potential (MMP) polarization are presented in human mononuclear cells with type 2 diabetes. 7 Moreover, mitochondria are the major source of reactive oxygen species (ROS), which are generally viewed as the toxic byproducts of aerobic metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…Exposure to glucose also results in increased levels of advanced glycation (glycosylation or glycoxidation) end products (AGEs) that can directly regulate endothelial cell permeability, monocyte migration, and ultimately promotes inflammatory gene expression, contributing to microvascular and macrovascular complications ( Goldin et al, 2006 ). Glucose levels also correlate with mitochondrial transmembrane potential in peripheral blood leukocytes attained from human Type I diabetics ( Matteucci et al, 2011 ), an increase of which results in elevated superoxide production that may directly contribute to cell damage ( Brownlee, 2001 ).…”
Section: Introductionmentioning
confidence: 99%